PENGARUH GREEN ACCOUNTING, SALES GROWTH DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Lyandra Aisyah Margie; Mayura Melinda (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to test and analyze the effect of Green accounting, Sales growth, and Tax avoidance on firm value in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. This type of research is quantitative research. The population in this study amounted to 87 companies, the sample selection in this study used the Purposive sampling method, namely the selection of samples based on predetermined criteria, obtained as many as 51 data observations The test results in the study indicate that simultaneously green accounting, sales growth and tax avoidance have a significant effect on firm value. Partially green accounting has a significant effect on firm value, while sales growth and tax avoidance have no significant effect on firm value